Encapsulating Azolates Within Cationic Metal–Organic Frameworks for High‐Energy‐Density Materials - Ning Ding; Chaofeng Zhao; Jichuan Zhang; Yao Du; Qi Sun; Shenghua Li; Siping Pang (Advanced Science)
Abstract Despite the synthesis of numerous cationic metal‐organic frameworks (CMOFs), their counter anions have been primarily limited to inorganic Cl−, NO3−, ClO4−, BF4−, and Cr2O72−, which have weak coordination abilities. In this study, a series of new CMOFs is synthesized using azolates with strong coordination abilities as counter anions, which are exclusively employed as ligands for coordinating with metals. Owing to the unique nitrogen‐rich composition of azolates, the CMOFs demonstrate significant potential as high‐energy‐density materials. Notably, CMOF(CuTNPO) has an exceptionally high heat of detonation of 7375 kJ kg−1, surpassing even that of the state‐of‐art CL‐20 (6536 kJ kg−1). To further validate the advantages of employing azolates as counter anions, analogues with azolates serving as ligands are also synthesized. The comparison study indicates that encapsulating azolates within the cationic frameworks confers both high energy and safety properties. X‐ray data and quantum calculations indicate that their enhanced performance stems from stronger H─bonds and π–π interactions. This study introduces new roles for azolates in MOFs and expands possibilities for structural diversity and potential applications of framework materials.